Replicating the Success of KB Villages: A Mock Study of Mamasa District as a Development Model in Lempangang Village - Al Ayyubi, Ibnu Imam; Nurhikmah; Prayetno, Eko; Nurfajriyah, Dewi Syifa; Fitriani, Sri Ayu (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research discusses the success of the family planning village that has been implemented in Lempangan Village, Gowa Regency, in significantly reducing stunting rates. This study uses a descriptive qualitative approach to describe the success factors of this programme. The results show that active community participation, collaboration between the village government, community health centres, and related institutions, and the use of technology in health education are the main keys. In addition, a family-based approach that involves all family members in maternal and child health management also plays an important role in overcoming the problem of stunting. The KB Village model in Lempangang Village can be used as an example for other regions in an effort to reduce stunting and improve the quality of life of the community in a sustainable manner.